Managerial of School Principals to Create Effective Schools (Study at Islamic Junior High School) - Zamroni, Muhammad; Barnoto (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
School leaders play an important role in the implementation of teaching in the classroom. SMPI Sabilurrosyad in Mojokerto which is located at Jalan Raya Kartini. Number 19 was established in 2007 and currently has 6 classes with a total of 150 students, supported by 21 teaching staff and 6 educational staff. This is directly related to the managerial ability of the principal. Therefore, the researcher wants to analyze the managerial management of Islamic junior high school principal Sabilurrosyad Jetis Mojokerto planning the effectiveness of learning. The formulation of the problems in this study are: 1) How does the managerial of the Sabilurrosyad Jetis Mojokerto Islamic junior high schoolhead plan the effectiveness of learning? 2). How does the managerial of the Sabilurrosyad Jetis Mojokerto Islamic junior high school principal implement learning effectiveness? 3). What are the managerial results in the implementation of learning evaluation at Sabilurrosyad Jetis Mojokerto Islamic junior high school? By using this type of qualitative research. After conducting research the researchers found the results, namely 1). The managerial ability of the principal in making school improvement plans in accordance with effective school standards. 2). Sabilurrosyad Jetis Mojokerto Islamic junior high school leadership skills in effectively managing the institution according to procedures, such as having a different organizational structure that clearly describes roles, tasks and functions, especially by issuing assignment letters and decisions. 3). head of Islamic junior high school Sabilurrosyad, has successfully used his managerial skills to build an effective school with a myriad of achievements achieved Islamic junior high school Sabilurrosyad Jetis Mojokerto.